Oral fluoride retention after professional topical application in children with caries activity: comparison between 1.23% fluoride foam and fluoride gel - Cecília Claudia Costa Ribeiro; Ana Emília Figueiredo de Oliveira; Fernanda Ferreira Lopes; Lívia de Almeida Barros (Faculdade São Leopoldo Mandic, 2008)
Objective: This study evaluated fluoride retention in the saliva of children with caries activity after topical fluoride application in the form of gel and foam. Methods: A cross-sectional, blind and randomized study, conducted with ten caries-active children aged between 8 and 10 years, in two stage, with a washout interval of two weeks between them. The treatments consisted of: a) application of 2mL acidulated phosphate fluoride of the gel type in a mold and b) application of 2mL acidulated phosphate fluoride of the foam type in a mold. After the washout, the treatments were inverted. Non-stimulated saliva was collected from the children at the times of 5, 15, 30 and 60 minutes after topical fluoride application. For statistical analysis the Student's-t test was used, with a level of significance of 5%. Results: Saliva analysis was performed using a fluoride-specific electrode (ISE25F/ Radiometer, Copenhagen, Denmark) at the Aquatic Science Center of the Federal University of Marana, which revealed differences after 5 minutes (p=0.0055) and 15 minutes (p=0.0208). The topical application of fluoride in the gel form revealed a higher concentration of fluoride in the saliva. Conclusion: There were differences in the retention of fluoride in the saliva of children with caries activity after the topical application of fluoride gel and the topical application of fluoride foam after 5 and 15 minutes of their application. The topical application of fluoride foam is recommended, on the basis of the lower probability of toxicity during its use.